PENGEMBANGAN BAHAN AJAR VIRTUAL REALITY MATA KULIAH PRAKTIK BAHAN BANGUNAN BERBASIS KEBUTUHAN INDUSTRI ERA SOCIETY 5.0 - Liana Atika; Dwiki Muda Yulanto; Siti Ulgari (LPPM Universitas Negeri Jakarta, 2023)
This research aims to create a collaborative and participatory classroom atmosphere in the use of technology in the world of Education. The era of Society 5.0 makes educators minimize their role as Learning material providers to become educators as an inspiration for the growth of student creativity. This study examines the validity and effectiveness of virtual reality teaching materials for building materials practice courses based on the needs of industry Society 5.0. This research used a research and development (R&D) approach with the ADDIE development model (Analyze et al., Evaluation). This study resulted in media feasibility from several experts where the learning design score was 3.85, learning material expert 3.77, media design expert 3.86; and the increase in student learning outcomes using media with an average pretest score of 41.12 and an average post-test of 74.80 seen from these values, the learning outcomes of students in building materials practice courses using virtual reality media increased by 33.68 or 87.77%.